Sul fronte del ritorno. Trasmissione del trauma nella letteratura italiana contemporanea - Giancarlo Alfano (Laboratoire Italien)
The article offers an interpretation of part of the Italian literary production from the early decades of this century, starting from the subject’s relationship with family lineage and collective history. In some poets, novelists and comic artists, the comparison with the generational sequence is interpreted as a way of depicting the entirety of post-war Italian history. In this way, elements that may seem chronologically outdated or even non-pertinent in contemporary life take on the character of what Francesco Orlando called the ‘return of the repressed’, starting with the trauma of the war.